Body composition and anthropometric parameters of premature infants with very low and extremely low body weight at full-term age (38-40 weeks post-conceptual age) - Evgeniia L. Pinaeva-Slysh; Vera A. Skvortsova; Tatyana E. Borovik; Milana A. Basargina; Elena P. Zimina; Olga L. Lukoyanova; Maria S. Illarionova; Nataliya A. Kharitonova (Лечащий Врач)
Background. In the complex treatment of premature infants, nutrition plays an important role, the adequacy of which largely determines their growth and development.Objective. Assessment of anthropometric parameters and body composition of children with very low and extremely low body weight at birth and at 38-40 weeks of postconceptional age.Materials and methods. We conducted a cohort ambispective randomized study. It included 70 premature babies (28 girls and 42 boys), born with a body weight of less than 1000 g (group 1, n = 40) and from 1000 to 1500 g (group 2, n = 30). Anthropometric data at birth and at the time of the study were assessed using international growth standards INTERGROWTH–21st. The amount and ratio of fat and lean body mass were determined using air plethysmography.Results. When assessing the nutritional status of premature infants of both groups at term (38-40 weeks of postconceptual age), a significant decrease in standardized z-scores was found – weight, body length and head circumference for age in group 1, as well as weight and head circumference by age in the 2nd group, more pronounced in the 1st group. Malnutrition (z-score of body weight for age less than 1 SD) was detected in 77.5% of children in group 1 and 23.3% in group 2. Analysis of body composition indicators did not reveal significant differences in the percentage of fat and lean body mass in children of groups 1 and 2, but lean body mass was 440 g less in children with extremely low birth weight. In group 1, statistically significant direct correlations were established between the z-score of body weight and lean body mass, expressed both as a percentage and in kg, as well as a significant inverse correlation with body fat mass as a percentage.Conclusion. The formation of postnatal growth retardation in a significant proportion of children born weighing less than 1500 g dictates the need for careful dynamic monitoring of their nutritional status for timely correction.